Post-COVID-19 vaccination and the brain: A critical analysis of CNS MRI findings - Ghaderi, Sadegh; Mohammadi, Sana (Trends in Immunotherapy, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has led to an urgent need for vaccine development and global distribution. Recent research suggests that there may be potential impacts on the central nervous system (CNS), as evidenced by findings from magnetic resonance imaging (MRI). This article aims to provide feedback on the current evidence regarding the associations between COVID-19 vaccination and neurological complications. It is essential to conduct further research to enhance our scientific understanding of how vaccines interact with the central nervous system. This knowledge can significantly support public health efforts in controlling the spread of new viral variants through widespread vaccination.